Hubungan Pola Asuh Orang Tua dengan Tipe Kepribadian DISC pada Peserta Didik Kelas XI IPS 2 di MAN 2 Cilegon - Putri Rahma Cantika; Astria Nova Khoirini; Elvira Khairunnisa; Tia Fairuz Nabilah; Indah Fitriyani; Hunainah (STKIP Subang, 2026)
Differences in students' personalities are influenced by various factors, while parenting styles are suspected to play a role in character and personality formation. This study aims to determine the relationship between parenting styles and DISC personality types among students. The research uses a quantitative approach with a correlational design involving 23 students. Data were collected thru a parental upbringing questionnaire and the DISC instrument, which measures the types of Dominance, Influence, Steadiness, and Compliance, then analyzed descriptively and tested using Chi-Square at a significance level of 0.05. The most dominant parenting style is democratic at 73.9%, while the most commonly found personality type is Compliance at 43.5%, followed by Steadiness at 34.8%. The Chi-Square test results show that the calculated χ² value of 5.63 is smaller than the table χ² value of 12.59, indicating that there is no significant relationship between parenting style and DISC personality type among the students. The relationship between parenting styles and DISC personality types among students was not significantly proven in this study.